Analysis of patients' reports to the oncological surgery clinic - Piotr Krajewski; Agata Krajewska; Magdalena Żukowska (Journal of Education, Health and Sport, 2018)
In the Polish healthcare system, the primary care physician is responsible for directing patients to outpatient specialist care if such need occurs. This is usually performed basing on the physical and subjective examination alone, because often it is not possible to perform more advanced diagnostic imaging that can confirm or rule out a disease requiring specialist intervention. Cancer diseases are a group of diseases where the time from diagnosis to treatment is particularly important and plays a key role in prognosis. Oncological surgery is a field of medicine, that deals with the surgical treatment of a close group of cancers.